Ação do mercúrio no Sistema Hepatonefrocítico de operárias de Bombus atratus (Hymenoptera: Bombini) - Balsamo, Paulo José (2020)
In addition to environmental stressors, native Brazilian bees are continuously exposed to biotic stressors, such as parasites and pathogens, and abiotic stressors, such as pesticides and metals. Metallic contaminants such as mercury (Hg), have the ability to induce bees to generate reactive oxygen species (ROS), causing the formation of oxidative stress. In this context, the labeling of enzymes related to the cellular response was studied, specifically chaperones (Heat Shock Proteins) Hsp70 and Hsp90, cytochrome P450 and superoxide dismutase (SOD) in cells of the Hepato-Nephrocytic System (HNS) of Bombus atratus, exposed to Hg. Workers of B. atratus were collected in the municipality of Sorocaba, SP, (23º34'53.1''S 47º31'29.5 ''W), during the months of February to March 2017, 2018 and 2019. After the collection, the workers were placed individually in boxes for the toxicological test and kept in an incubator at 26° C, 70% humidity, in the dark, for 48 hours, according to OECD recommendations. Eleven workers were used for each group, being offered both solid food (soy extract, honey and pollen, 1: 1: 1 ratio) and the exposed group 2mL of a Hg solution at a concentration of 110 µg L-1, (110ppb Hg) and to the control group uncontaminated water. After 48 hours the animals were cryo-euthanized and the tissues that make up the HNS were dissected and processed for morphological and immunofluorescence analyzes. When compared to control bees, the exposed group showed increased P450 and SOD marking, indicating the role of trophocytes and oenocytes in the first response to metal contamination, represented by the increased expression of phase I detoxification enzymes (P450) and primary response to oxidative stress (SOD). The chaperones Hsp70 and Hsp90 had a reduction in labeling, a fact that may be linked to the origin of the collection of bees in the field for experimentation. These data corroborate the thesis that the Hepatonephrocytic System is a stress biomarker and the expression of enzymes by cells of this system can serve as a cellular marker of the physiological status of native Brazilian bees.